2014
DOI: 10.1111/cts.12246
|View full text |Cite
|
Sign up to set email alerts
|

MOR1 Expression in Gastric Cancer: A Biomarker Associated With Poor Outcome

Abstract: Background: At present, the expression of MOR1 and its function in gastric cancer remains unclear with evidence suggesting that it is to be involved in tumor progression and metastasis. The study was to assess the clinicopathologic relevance and prognostic value of MOR1 expression in gastric cancer. Methods: Real-time quantitative RT-PCR and immunohistochemical staining were used to detect MOR1 expression in primary gastric cancerous surgical specimens and adjacent nontumorous tissues. Results: High MOR1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
2
26
0
1
Order By: Relevance
“…The mu-opioid receptor (MOR) has been shown to be widely distributed in limbic and cortical regions such as the NAcc 18,19 . Therefore, we wanted to first demonstrate the presence of MOR in NAcc neurons of the mouse by targeting the most common MOR isoform, MOR1 20 . The anti-MOR1 antibody conjugated with FITC was used in conjunction with DAPI nuclear stain.…”
Section: Colocalization Of Gad67 and Mor1 In Mouse Naccmentioning
confidence: 99%
“…The mu-opioid receptor (MOR) has been shown to be widely distributed in limbic and cortical regions such as the NAcc 18,19 . Therefore, we wanted to first demonstrate the presence of MOR in NAcc neurons of the mouse by targeting the most common MOR isoform, MOR1 20 . The anti-MOR1 antibody conjugated with FITC was used in conjunction with DAPI nuclear stain.…”
Section: Colocalization Of Gad67 and Mor1 In Mouse Naccmentioning
confidence: 99%
“…Proteomic analysis with 2-DE can simultaneously detect changes of multiple proteins in plasma often detected differentially expressed proteins are common abundant plasma proteins and their diagnostic value may be limited. Twodimensional electrophoresis (2-DE) has been used for the discovery of circulating auto-antibodies in cancer patients and annexins I and II were reported as specific antigens in sera from patients with lung [Nolen and Lokshin, 2013]; b-2 microglobulin [Yang et al, 2009] apolipoprotein [Podzielinski et al, 2013]; gene-expression in HE4 [Ferraro et al, 2013 [Du et al, 2013]; AGR2 [Li et al, 2015c]; ubiquitin ligase [Goka and Lippman, 2015]; ferritin light chain [Jezequel et al, 2012] Gastric cancer a1-antitrypsin precursor [Hsu et al, 2007]; pepsinogen C [Terasawa et al, 2014]; Cathepsin B [Ebert et al, 2005]; galectin-1/-3 [Thijssen et al, 2015]; miR-214 [Zhang et al, 2015b]; angiopoietinlike protein 2 [Yoshinaga et al, 2015]; MOR1 [Yao et al, 2015]; circular RNA [Li et al, 2015a] Liver cancer Galectin-1/-3 [Thijssen et al, 2015]; CHI3L1/MASP2 [Ding et al, 2014]; Sall4, Glypican-3, dickkopf-1 and talin-1 [Chatterjee and Mitra, 2015] …”
Section: Plasma Proteomics In Tumorsmentioning
confidence: 99%
“…Fibrinogen A fragment [van den Broek et al, 2010]; BAG6, DDX39, ANXA8, COX4 [Calderon-Gonzalez et al, 2015]; GCDFP-15 [Darb-Esfahani et al, 2014]; Versican [Du et al, 2013]; AGR2 [Li et al, 2015c]; ubiquitin ligase [Goka and Lippman, 2015]; ferritin light chain [Jezequel et al, 2012] Gastric cancer a1-antitrypsin precursor [Hsu et al, 2007]; pepsinogen C [Terasawa et al, 2014]; Cathepsin B [Ebert et al, 2005]; galectin-1/-3 [Thijssen et al, 2015]; miR-214 [Zhang et al, 2015b]; angiopoietinlike protein 2 [Yoshinaga et al, 2015]; MOR1 [Yao et al, 2015]; circular RNA [Li et al, 2015a]…”
Section: Breast Cancermentioning
confidence: 99%
“…Concurrent translational investigation has revealed that increased expression of µ-opioid receptors (MOR) in non-small cell lung cancer [3], prostate cancer [4], gastric cancer [5] and melanoma [6, 7] is associated with greater degree of metastasis [8]. Further laboratory work reveals multiple interactions between opioids and transcription factors for tumor growth, immunomodulation and vascular endothelial growth factor (VEGF) expression, leading to modulation of neovascularization [9].…”
Section: Introductionmentioning
confidence: 99%